Core Dynamics for the Mass Communication History Course. (September 2019) - Ingold, Charles H.
Considering King's "core knowledge" for college courses in journalism history, a set of "core dynamics " is proposed to provide additional perspective and suitability for courses in general mass communication history. The core dynamics approach aims to help media history courses impart advanced understanding of what forces, patterns, and processes have made things the way they are in the mass media, and in addition provides a framework for understanding current and future developments as they unfold.